An Analytical Study on Socio-Economic Status of Women Employees as a Teacher: Exploring the Relationship between Socio-Economic Status and Employment of Women Teachers (Journal of Advances and Scholarly Researches in Allied Education, 2019)
The point of this study is to choose the distinction between the economic and cultural position, the association between the fragment status of women teachers and their economic prosperity. For this study the A pilot test was conducted and corrections were made in the questionnaire, as were other sources, for example, journals, papers, diaries , reports, articles and related investigations. The scientist gathered information from 300 female respondents picked utilizing a delineated irregular inspecting method. Among the 300 women respondents, 245 are working on a regular basis and 55 are on temporaryGuest basis. Random sampling method to distribute questionnaires was followed by the researcher, and user data was obtained. From the study one can see that strong measures are expected to upgrade the socio-economic status of women instructor employees.